2018
DOI: 10.1186/s12884-018-1992-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sensitivity of placental growth factor and soluble fms-like tyrosine kinase 1 at 36 weeks’ gestation to predict small-for-gestational-age infants or late-onset preeclampsia: a prospective nested case-control study

Abstract: BackgroundFetal growth restriction is a disorder of placental dysfunction with three to four-fold increased risk of stillbirth. Fetal growth restriction has pathophysiological features in common with preeclampsia. We hypothesised that angiogenesis-related factors in maternal plasma, known to predict preeclampsia, may also detect fetal growth restriction at 36 weeks’ gestation. We therefore set out to determine the diagnostic performance of soluble fms-like tyrosine kinase 1 (sFlt-1), placental growth factor (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Therefore, it was conceivable that measuring these placental biomarkers in maternal blood could be used in the prediction of pre-eclampsia and fetal growth restriction. 6,9 The serum sFlt-1/PlGF ratio has already been used in improving the clinical management for preeclampsia. Pre-eclampsia is defined as the new onset of hypertension and proteinuria after 20 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was conceivable that measuring these placental biomarkers in maternal blood could be used in the prediction of pre-eclampsia and fetal growth restriction. 6,9 The serum sFlt-1/PlGF ratio has already been used in improving the clinical management for preeclampsia. Pre-eclampsia is defined as the new onset of hypertension and proteinuria after 20 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Although most research utilising the sFlt-1/PlGF ratio in placental dysfunction has been targeted at preeclampsia [21], more recent work has been investigating the use of these biomarkers for detecting other pregnancy complications such as the identification of SGA babies [35][36][37], fetal compromise associated with RFM [18] and gestational hypertension and placental abruption [38]. It is likely that interest will increase in the use of biomarkers combined with other aspects of care for the management of RFM after results from the AFFIRM trial indicated that a care package for RFM did not significantly reduce the rate of stillbirth but increased the rate of obstetric intervention [39].…”
Section: Discussionmentioning
confidence: 99%
“…FLAG study design overview 38 . This study is part of the Fetal Longitudinal Assessment of Growth (FLAG) study Women carried out at the Mercy Hospital for Women, a tertiary maternity hospital in Melbourne with approximately 6000 births annually.…”
Section: Methodsmentioning
confidence: 99%